ANALISIS FAKTOR YANG BERPENGARUH TERHADAP KONVERSI SPUTUM BASIL TAHAN ASAM PADA PENDERITA TUBERKULOSIS - Clevia Revi Maretha Mahendrani; Mohammad Subkhan; Annisa Nurida; Kartika Prahasanti; Yelvi Levani (Journal Medical Universitas muhammadiyah Makassar, 2020)
Tuberculosis (TB) is caused by bacteria (Mycobacterium tuberculosis) that most often affect the lungs. The incidence of tuberculosis in Indonesia is high because the success rate of tuberculosis treatment has decreased which causes the chain of transmission continues to occur. The main government programs to decrese the incidence and increasing the success treatment with the Directly Observed Treatment (DOTS) program. One important indicator of the DOTS program to assessing the success of tuberculosis treatment is the conversion of positive AFB sputum to negative at the end of the intensive phase of treatment. AFB sputum conversion to negative at the end of the intensive phase of treatment is influenced by several internal factors such as level of education and income, gender, adherence, patient's nutritional status, and comorbidities. Then external factors can also influence the AFB sputum conversion in anti-tuberculosis treatment such as environmental conditions, smear positivity, drug taking supervisors (PMO), and availability of drugs in health facilities.